University students academic stressor / Nur Azleen Abdullah, Nur Nabilah Berhan and Qysty Ahmad Shukri - Abdullah, Nur Azleen; Berhan, Nur Nabilah; Ahmad Shukri, Qysty (2019)
Nowadays, stress is a common problem in everyone's daily life. Stress is not a new thing or new phenomenon. At some point of time in most of people lives, they encounter stress or anxiety, especially students due to all the pressures that they need to go through in their academic world. As students, they need to manage their time well within study and their social life. Chasing for good grades in their exam puts undue and unnecessary pressure on students. There were suicide cases among students because they cannot handle pressure. The objectives of this study are to build model of academic stressors and identify academic stressors that can contribute to stress among students of Faculty of Mathematics and Computer Sciences in Universiti Teknologi Mara Seremban Campus. This study used Logistic Regression as a method to analyse data for presence of stress. The study used self-administered questionnaire. The questionnaire was adapted from 2 different questionnaires which are Kessler Psychological Distress Scale (K 10) by Kessler R. and Survey of college academic stressors by Glenn M. Calaguas. There are seven factors that were chosen in this study which are related to subject, schedule, classroom, lecturer, classmate, financial and others expectations. This study have found two factors that contribute to the presence of stress among university students which are subject and expectations. This study indicates that 59.42% of students are stress and the other 40.58% students are not stress.